1991
DOI: 10.1128/aac.35.7.1309
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aminoglycosides with the outer membranes and purified lipopolysaccharide and OmpF porin of Escherichia coli

Abstract: The mechanism of uptake of aminoglycosides across the outer membrane of Escherichia coli was reevaluated. Porin-deficient mutants showed no alteration in gentamicin or kanamycin susceptibility. Furthermore, the influence of kanamycin on intrinsic tryptophan fluorescence of porin OmpF (Y. Kobayashi, and T. Nakae, Eur. J. Biochem. 151:231-236, 1985) was shown to be strongly influenced by protein concentration and EDTA. This led to the hypothesis that aminoglycoside-mediated increases and decreases in intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
154
2
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 34 publications
4
154
2
3
Order By: Relevance
“…Foulds and Chai reported that E. coli cells defi cient in ompF were more resistant to kanamycin and gentamicin (Foulds and Chai, 1978). On the other hand, Hancock et al reported that porin-defi cient mutants show no alteration in susceptibility to these antibiotics (Hancock et al, 1991). In addition to these observations, Kashiwagi et al reported that aminoglycosides are transported into cells by the oligopeptide transport system (Kashiwagi et al, 1998).…”
Section: Susceptibility Of the Test Cells To Antibioticsmentioning
confidence: 87%
“…Foulds and Chai reported that E. coli cells defi cient in ompF were more resistant to kanamycin and gentamicin (Foulds and Chai, 1978). On the other hand, Hancock et al reported that porin-defi cient mutants show no alteration in susceptibility to these antibiotics (Hancock et al, 1991). In addition to these observations, Kashiwagi et al reported that aminoglycosides are transported into cells by the oligopeptide transport system (Kashiwagi et al, 1998).…”
Section: Susceptibility Of the Test Cells To Antibioticsmentioning
confidence: 87%
“…Contrarily, hydrophobic substances are supposed to diffuse through the cell wall and the IM but to a minor degree through the OM that seems to be an efficient barrier for hydrophobic substrates in Mycobacteria (8). Another process is described for the uptake of polycationic compounds (which comprise many antibiotics or diethylaminoethyl-or polylysinmoieties) which are thought to disorganize the OM, thereby mediating their own uptake in a process termed 'self-promoted uptake' (13). Moreover, many molecules can be specifically channeled into the cell by transporter proteins using energy-dependent processes or facilitated diffusion systems (for overview see (8)).…”
Section: Cell Wallmentioning
confidence: 99%
“…Our finding that polyamines can drastically affect porinmediated fluxes is important because it shows that (i) porins are functionally regulated channels and (ii) polyamines and related compounds could potentially serve as therapeutic agents specifically targeted at the outer membrane. Although the outer membrane is an effective barrier against hydrophilic and many hydrophobic compounds, some types of antibiotics, such as polymyxin B and aminoglycosides, have been shown to enter the cells by increasing outer membrane permeability (10,11,35). In their studies of polycation-induced sensitization of bacteria to antibiotics, Vaara and Vaara (36) reported that, as opposed to cations bearing a large number of positive charges (5 to 50), cadaverine, spermine, and spermidine were neither bactericidal nor active as outer membrane permeability-increasing agents.…”
Section: Discussionmentioning
confidence: 99%